Productive energy cycles in mentoring relationships: A qualitative investigation - Ursula Liebhart (Zeitschrift für Personalforschung (ZfP), 2013)
Cross-Company Mentoring is an external form of business mentoring across organizational borders. Thereby it is important that the participants are able to quickly get into a high quality developmental relationship to reap the benefits of the learning opportunities. This paper thus focuses on the influence and impact of an essential power, namely the human energy that emerges and flows between two interactive individuals. Based on a study that provides a unique dyadic and qualitative empirical examination of the development of mentoring relationships, the relationship between the perceived energy level of 13 mentoring tandems and their outcomes are examined. The mentoring tandems are classified into high, medium and low-performing tandems. Similarities and differences between these performance groups as well as same-gender and crossgender tandems are worked out. Suggestions for a reflected and successful development of sustainable relationships are made. – – Cross-Company Mentoring ist ein interorganisationales Programm für die Zeitspanne von zwölf Monaten, in dem Teilnehmer aus unterschiedlichen Organisationen in Tandems zusammengestellt werden. Es ist wichtig, dass die Teilnehmer schnell in eine hoch-qualitative Mentoringbeziehung einsteigen können, um die Vorteile aus den Lernmöglichkeiten umsetzen zu können. Deswegen fokussiert dieser Beitrag auf den Einfluss und die Wirkung einer essentiellen Kraft, nämlich der humanen Energie, die zwischen zwei interaktiven Personen entsteht und fließt. Basierend auf einer qualitativen empirischen Untersuchung der Entwicklung dieser Lernbeziehungen, wird der Zusammenhang zwischen dem wahrgenommenen Energieniveau der Tandems und deren Ergebnisse untersucht. Die Ergebnisse erlauben konkrete Vorschläge zur reflektierten und erfolgreichen Entwicklung von nachhaltigen Beziehungen.
Keywords: M10; M12; M53; 650; energy and performance; dyadic relationship; cross-company mentoring; Coaching; Soziale Beziehungen; Geschlecht; Österreich